2014
DOI: 10.17509/bs_jpbsp.v14i2.723
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Listening: Let Students Experience Learning by Optimizing the Use of Authentic Materials

Abstract: In a country like Indonesia, one of challenges in learning English as a foreign language is a lack of exposure of English in its authentic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…In reading using experimental study found that AM implementation increase students' interest in reading (Aryati & Anggaira, 2016);Firmansyah 2015). In listening, the use of AM is proven to be effective in increasing students' listening comprehension (Octasari& Hastini, 2014;Hapsari& Ratri, 2014). Positive impacts also found in writing skills by improvements in three aspects; content, language use and vocabulary (Mardanigsih, Ida & Fitri, 2015).…”
Section: Authentic Materials In Indonesian Contextmentioning
confidence: 99%
“…In reading using experimental study found that AM implementation increase students' interest in reading (Aryati & Anggaira, 2016);Firmansyah 2015). In listening, the use of AM is proven to be effective in increasing students' listening comprehension (Octasari& Hastini, 2014;Hapsari& Ratri, 2014). Positive impacts also found in writing skills by improvements in three aspects; content, language use and vocabulary (Mardanigsih, Ida & Fitri, 2015).…”
Section: Authentic Materials In Indonesian Contextmentioning
confidence: 99%
“…These are related to speed, complex sentences, missing the subsequent information, long sentences, new broadcasts, speaker accent, background noise, word recognition, new words, and phonetic variations [2]. These difficulties seem unmotivated the learners in listening class [3]. These complexities are commonly found in English language learning in which English is the second or foreign language of the learners.…”
Section: Introductionmentioning
confidence: 99%
“…Ridel (2003) argues that among these skills, listening is considered the hardest skill to be learnt (as cited in Hapsari & Ratri, 2013). To overcome this, it is suggested that authentic materials of listening are given to the students, even from the beginning of a language course, in order to give the students benefits of naturalness and real-life listening experience; listening to authentic materials exposes students with natural accent, speed, and meaning (Field, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…(Hapsari & Ratri, 2013). It can be caused by students' lack of familiarity to the accents and speech speed of the speakers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation